Inverse estimation of the unknown base heat flux in irregular fins made of functionally graded materials. (October 2017) - Chen, Wen-Lih; Chou, Huann-Ming; Yang, Yu-Ching
Abstract: In this study, an inverse algorithm based on the conjugate gradient method and the discrepancy principle has been successfully applied to an irregular fin made of functionally graded materials to estimate the unknown base heat flux distributions by using temperatures at some measurement locations. The inverse results, in which three different base heat flux distributions are to be determined, have proven current method's capability to accurately estimate arbitrary fin-base heat flux distributions even measurement errors have been taken into account. The temperature data calculated from the direct problem are used to simulate the measured temperature. The influence of measurement errors upon the precision of the estimated results is also investigated. This method does not need any prior information on the unknown quantity, and results show that excellent estimations can be obtained for the test cases considered in this study.